2020
DOI: 10.3389/fnmol.2019.00324
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Delta Opioid Receptors Mediate Formoterol Anti-allodynic Effect in a Mouse Model of Neuropathic Pain

Abstract: Peripheral Delta Opioid Receptors and Formoterol therefore, extends our previous results by confirming that changes in the mechanical threshold are associated with changes in peripheral DOP profile. It also highlights the common impact on DOP receptors between serotonin noradrenaline reuptake inhibitors such as duloxetine and the β2 mimetic formoterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(75 reference statements)
1
5
0
1
Order By: Relevance
“…DORs are necessary to the antiallodynic action of chronic treatments with antidepressant drugs (Benbouzid et al, 2008a;Ceredig et al, 2018;Choucair Jaafar et al, 2014;Kremer et al, 2016;Kremer et al, 2018) and with β 2 adrenoceptor agonists (Ceredig et al, 2020;Choucair Jaafar et al, 2014;Kremer et al, 2020). In agreement with these findings, we found here that the action of a chronic treatment with the PDE4i rolipram on mechanical hypersensitivity also required DORs.…”
Section: Discussionsupporting
confidence: 90%
“…DORs are necessary to the antiallodynic action of chronic treatments with antidepressant drugs (Benbouzid et al, 2008a;Ceredig et al, 2018;Choucair Jaafar et al, 2014;Kremer et al, 2016;Kremer et al, 2018) and with β 2 adrenoceptor agonists (Ceredig et al, 2020;Choucair Jaafar et al, 2014;Kremer et al, 2020). In agreement with these findings, we found here that the action of a chronic treatment with the PDE4i rolipram on mechanical hypersensitivity also required DORs.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest a mechanism similar to the one previously observed for antidepressant drugs, whose antiallodynic action has also been shown to be dependent upon DOP receptors. 9,16,19 In the Cuff model, it was also shown that sustained neuropathic pain condition was associated with a reduction of DOP receptor expression in small calcitonin gene-related peptide positive primary sensory neurons and in free nerve endings, that was not present in duloxetine 19 treated animals and that was partly corrected in formoterol 38 treated animals. In physiological conditions, DOP receptor agonists have little noticeable effect on nociception, as shown by pharmacological studies and data in DOP receptor deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the inhibition of Ca 2+ or Na + current, and subsequent inhibition of peripheral sensory neurons, which ultimately produces analgesia (Stein et al, 2003). In a variety of preclinical pain models such as inflammatory and neuropathic pain, the opioid receptors in the DRG are upregulated (Puehler et al, 2006;Ceredig et al, 2019). In addition, opioids produce more significant analgesic effects in injured tissues than in non-injured tissues (Stein et al, 2003;Vanderah et al, 2008).…”
Section: Discussionmentioning
confidence: 99%